Export Growth and Factor Market Competition: Theory and Some Evidence - Julian Emami Namini; Giovanni Facchini; Ricardo A. Lopez (Tinbergen Institute, 2011)
Empirical evidence suggests that sectoral export growth decreases exporters' survival probability, whereas this is not true for non-exporters. Models with firm heterogeneity in total factor productivity (TFP) predict the opposite. To solve this puzzle, we develop a twofactor framework where firms differ in factor intensities. Thus, export growth increases competition for the factor used intensively by exporters, eliminating some of them, while non-exportersbenefit. Interacting heterogeneity in factor shares with heterogeneity in TFP we show that factor market competition reduces the growth in average TFP brought about by trade liberalization.
Keywords: F12; F14; F16; L11; 330; Firm dynamics; two-factor trade model; firm heterogeneity in factor input ratios; Produktivität; Internationaler Wettbewerb; Produktionsfaktor; Wirtschaftsmodell; Theorie